[Discussion of Auditor's Loss Functions Implicit in Consumption-Investment Models]: A Reply - Scott, William R. (Journal of Accounting Research, 1975)
William R. Scott, [Discussion of Auditor's Loss Functions Implicit in Consumption-Investment Models]: A Reply, Journal of Accounting Research, Vol. 13, Studies on Statistical Methodology in Auditing (1975), pp. 124-125